Rapidly-formed thermal runaway protection material and composition
By placing thermal runaway protection materials with high enthalpy value heat-absorbing materials between batteries, the chain reaction problem caused by thermal runaway of lithium-ion and sodium-ion batteries is solved, and effective suppression of thermal runaway and prevention of battery pack fire and explosion are achieved.
Patent Information
- Application Number
- CN202411129361.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-16
- Publication Date
- 2024-12-13
AI Technical Summary
Existing lithium-ion and sodium-ion batteries are prone to trigger chain reactions and cause fire or explosion in thermal runaway situations. Existing thermal management solutions such as aerogels, phase change materials and liquid-cooling systems cannot effectively prevent the diffusion and propagation of thermal runaway.
Using a rapid-forming thermal runaway protection material, containing 71-95% heat-absorbing material, 1.5-12% polyvinyl alcohol, 0-1% long-chain alkyl diacid and 3-16% UV curing package The resin is molded by ultraviolet light curing to form a high enthalpy material to absorb heat and prevent heat transfer.
When the battery is thermally out of control, the material has an enthalpy of heat absorption exceeds 1200J/g, and spontaneously endothermic decomposition forms a porous structure, effectively preventing adjacent batteries from heating up, avoiding fire and explosion, and can be customized and adapted according to the battery structure design.
Smart Images

Figure CN119119976A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of thermal runaway protection materials, and in particular relates to a rapid-prototyping thermal runaway protection material and a composition. Background Art
[0002] As a solution for high energy density storage, lithium-ion batteries have been widely used in portable energy storage devices and electric vehicles, and are considered to be the most competitive power source in future green smart grid energy storage. However, high energy density also brings high safety risks. The electrolyte and diaphragm components in existing lithium-ion batteries are flammable and explosive. In addition, the internal component distribution, uneven contact or external thermal abuse, mechanical abuse, and electrical abuse of lithium-ion batteries during operation will cause short circuits in the battery, release a large amount of heat, cause the battery to heat up rapidly and thermal runaway, cause toxic gas and smoke release, fire or even explosion, bringing great risks. In large-scale energy storage equipment, thermal runaway of a single battery will trigger a chain reaction in adjacent batteries, eventually causing a disaster. According to incomplete statistics, more than 60 safety accidents and multiple electric vehicle fire accidents have occurred in battery energy storage power stations around the world in the past decade. As the cost of raw materials for lithium-ion batteries continues to rise, sodium-ion batteries have become a research hotspot as a new generation of power batteries with lower theoretical costs, but sodium-ion batteries also have the problem of thermal runaway. This makes the improvement of lithium / sodium battery safety one of the important topics in the field of battery research.
[0003] The existing thermal management solutions are mainly as follows: (1) Using aerogel to separate each battery pack component. After a single battery pack has thermal runaway, the heat can be isolated within a limited range if it is not serious. However, aerogel cannot slow down the process of thermal runaway. When thermal runaway occurs, there is still a possibility of spillover to adjacent battery packs, resulting in continuous thermal runaway and fire or explosion. (2) Using phase change materials to manage the battery thermally. Usually, the phase change enthalpy value of phase change materials is only between 200 and 270 J / g, and after packaging, it is usually only between 100 and 200 J / g. Due to the low enthalpy value, phase change materials are usually used to maintain a constant operating temperature (such as 55°C) for the battery to maximize its performance, and cannot solve the problem of thermal runaway. (3) Installing a liquid cooling system on the battery and using a compressor to cool the battery. Due to the power limitation and feedback delay limitation of the compressor, the cooling efficiency of the liquid cooling system is limited and cannot cope with the instantaneous temperature rise.
[0004] Usually, in most cases of thermal runaway of battery packs, one battery goes into thermal runaway, then expands and generates huge heat, which squeezes and spreads the heat to the adjacent battery packs, causing thermal runaway of the adjacent battery packs, and finally spreads to the entire battery pack, causing fire and explosion. Therefore, if the thermal runaway battery can be blocked by a material to absorb heat and cool it down, preventing the thermal runaway of the adjacent battery packs from spreading, it will be able to effectively suppress the fire and explosion of the battery pack. Summary of the invention
[0005] In order to solve the deficiencies of the prior art, the main purpose of the present invention is to provide a fast-forming thermal runaway protection material and composition, which can be designed according to different battery structures, so that it is convenient to place between battery packs, or place one piece between a certain number of battery packs. The thermal runaway protection material of the present invention has a high endothermic enthalpy, and a chemical reaction will occur between 90-400°C and actively absorb heat. Usually, the battery pack will heat up quickly after thermal runaway, so that the thermal runaway protection material reaches above 90°C. At this time, the material will spontaneously endothermically decompose. Because the material has a high enthalpy value, it forms a continuous endothermic effect (the endothermic enthalpy of the endothermic material>1200J / g), which drives the temperature of the runaway battery pack to drop. After the decomposition of the protective material is completed, a porous structure will be formed, which becomes an excellent thermal insulation material, preventing heat from being transferred to adjacent batteries, preventing adjacent batteries from continuing to heat up, and avoiding fire and explosion.
[0006] To achieve the above purpose, the technical solution adopted by the present invention is:
[0007] A rapid prototyping thermal runaway protection material and composition, comprising, by mass percentage, 71-95% of a heat absorbing material, 1.5-12% of polyvinyl alcohol, 0-1% of a long-chain alkyl diacid, and 3-16% of a UV curing encapsulation resin; the preparation method thereof is as follows:
[0008] Add all the materials in the formula into a mixing kettle, mix them evenly, press them into shape in a mold, and cure them under ultraviolet light to obtain a thermal runaway protection material.
[0009] In the above technical solution, the ultraviolet lamp is a high-pressure mercury lamp or a metal halide lamp.
[0010] Specifically, the ultraviolet lamp is a 365nm-405nm ultraviolet lamp, including a composite ultraviolet lamp composed of one or more ultraviolet lamps in the 365nm band, the 385nm band, the 395nm band, and the 405nm band. The ultraviolet lamp is installed in a single-sided manner, aligned with the upper and lower surfaces, or staggered with the upper and lower surfaces. The irradiation power received by the surface of the thermal runaway protection material is greater than 30mW / cm 2 , irradiation dose>1J / cm 2 .
[0011] In the above technical scheme, the heat-absorbing material includes sodium acetate trihydrate, ammonium ferric oxalate trihydrate, citric acid monohydrate, citric acid, oxalic acid dihydrate, anhydrous oxalic acid, malonic acid, magnesium sulfate heptahydrate, zinc sulfate heptahydrate, succinic acid, maleic acid, fumaric acid, sodium carbonate decahydrate, calcium chloride hexahydrate, aluminum nitrate nonahydrate, ammonium pentaborate octahydrate, ammonium ferric sulfate dodecahydrate, ferrous chloride tetrahydrate, ammonium oxalate monohydrate, sodium tetraborate decahydrate, sodium tetraborate pentahydrate, aluminum sulfate 18hydrate, ammonium pentaborate, ammonium hydrogen borate tetrahydrate, boric acid, barium hydroxide octahydrate, pentahydrate and sodium silicate, silicic acid, hydrated silicic acid, ammonium aluminum sulfate dodecahydrate, hydrated sodium aluminum silicate, potassium aluminum sulfate dodecahydrate, sodium sulfate decahydrate, copper sulfate heptahydrate, ferrous sulfate heptahydrate, cobalt chloride hexahydrate, calcium sulfate dihydrate, etc. One or more, preferably with a mesh size of 80-300 meshes.
[0012] Preferably, the heat-absorbing material includes one or more of oxalic acid dihydrate, anhydrous oxalic acid, ammonium oxalate monohydrate, sodium acetate trihydrate, boric acid, ammonium pentaborate octahydrate, barium hydroxide octahydrate, sodium tetraborate decahydrate, potassium aluminum sulfate dodecahydrate, sodium sulfate decahydrate, calcium sulfate dihydrate, etc., and the preferred mesh size is 80-300 mesh.
[0013] In the above technical solution, the polyvinyl alcohol is a powder, preferably with a mesh size of 80-300. The polyvinyl alcohol structure contains a large number of hydroxyl groups and has good water absorption. The powder surface will absorb a small amount of water, which can react with the siloxane structure in the UV encapsulation resin to form a silanol structure, and then react with the hydroxyl group or crystal water on the surface of the heat-absorbing material to enhance the interface bonding strength between the encapsulation resin and the heat-absorbing material.
[0014] In the above technical scheme, the UV curing encapsulation resin comprises, by mass percentage: 25-70% of siloxane-epoxy resin composite modified polyurethane acrylate, 0-5% of epoxy resin, 5-40% of epoxy acrylate, 0-5% of acrylic acid, 5-30% of active monomer, 0-1% of long-chain alkyl diacid, 0-25% of silane modified resin, 0.1-3% of dewatering agent, 0-10% of spherical silicon powder, 0.1-3% of photoinitiator, and 0.01-0.3% of polymerization inhibitor. The preparation method is as follows: add the above components into a reactor according to the proportion, maintain stirring at 50-60°C for 2-3 hours, add the dewatering agent, and stir for 10-30 minutes to obtain the UV curing encapsulation resin.
[0015] Specifically, the above-mentioned epoxy resin refers to a substance containing epoxy bonds in its molecular structure, including one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol E epoxy resin, bisphenol S epoxy resin, epoxy soybean oil, cardanol-modified epoxy resin, trimethylolpropane triglycidyl ether, hexanediol diglycidyl ether, and phenyl glycidyl ether.
[0016] Specifically, the epoxy acrylate is a product obtained by ring-opening a mixture of acrylic acid and carboxyethyl acrylate in any proportion with the epoxy resin, including CN104 NS or CN120 NS of Sartomer.
[0017] Specifically, the above-mentioned active monomers are acrylate monomers with functions between 1 and 6 that do not contain a hydroxyl structure, including one or more of isobornyl acrylate, 2-cyclohexyl acrylate, 3,3,5-trimethylcyclohexyl acrylate, trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, tripropylene glycol diacrylate, dipropylene glycol diacrylate, 1,6-hexanediol diacrylate, isobornyl methacrylate, and tetrahydrofurfuryl methacrylate.
[0018] Specifically, the long-chain alkyl diacid includes one or more of dodecanedioic acid, tetradecanedioic acid, hexadecanedioic acid, octadecanedioic acid, and eicosanedioic acid; the long-chain alkyl diacid has a good dispersing effect on silicon powder.
[0019] Specifically, the above-mentioned silane-modified resin is a resin having an alkoxysilane group at the end group, and the alkoxysilane group includes trimethoxysilane, triethoxysilane, methyldimethoxysilane, and methyldiethoxysilane; the silane-modified resin includes one or more of silane-modified polyether resin, silane-modified polyacrylate resin, silane-modified polyurethane resin, silane-modified polyester resin, and alkoxy silicone resin.
[0020] Specifically, the dehydrating agent is toluenesulfonyl isocyanate, which can effectively remove residual moisture in the system, prevent hydrolysis of siloxane on the siloxane / epoxy resin composite modified polyurethane acrylate and silane modified resin structure, and improve the storage stability of UV curing encapsulation resin.
[0021] Specifically, the spherical silicon micropowder has a D50 of 50-300 μm and a D100 of less than 500 μm. Large particles of the spherical silicon micropowder can conduct ultraviolet light from outside to deep layers.
[0022] More specifically, when preparing a thermal runaway protection material having a thickness greater than 5 mm, spherical silicon powder is preferably added.
[0023] Specifically, the above-mentioned photoinitiator is a substance that can decompose or abstract hydrogen to generate free radicals under ultraviolet light, including 4-benzoyl-4'-methyl-diphenyl sulfide (BMS), 2,4,6-trimethylbenzoyldiphenylphosphine oxide (TPO), 2,4,6-trimethylbenzoylphosphonic acid ethyl ester (TPO-L), bis (2,4,6-trimethylbenzyl) phenylphosphine oxide (819), benzoin dimethyl ether (651), 2-methyl-1-(4-methylmercaptophenyl)-2-morpholine-1-propanone (907), poly[2-hydroxy-2-methyl -1-[4-(1-methylvinyl)phenyl]acetone], 2,4,6-trimethylbenzoyl-di(p-tolyl)phosphine oxide (TMO), 1-(9,9-dibutyl-9H-fluorene-2-yl)-2-methyl-2-morpholin-4-yl-propane-1-one, 1-hydroxycyclohexyl benzophenone (184), 4-acryloyloxybenzophenone, methyl o-benzoylbenzoate (OMBB) or more thereof; under the irradiation of ultraviolet light, the surface of the thermal runaway protection material will quickly solidify and form a material with a certain strength, which is conducive to subsequent transportation.
[0024] Specifically, the polymerization inhibitor is p-hydroxyanisole, so as to prevent the semi-adduct generated by the reaction of diisocyanate and hydroxy acrylate from polymerizing prematurely in the subsequent process.
[0025] Specifically, the preparation method of the siloxane-epoxy resin composite modified polyurethane acrylate is as follows:
[0026] S1: Add diisocyanate and hydroxy acrylate into reactor A in a molar ratio of 1:1, add 0.01-0.2% of the total mass of diisocyanate and hydroxy acrylate as catalyst (dibutyltin dilaurate), and 0.01-0.2% of the total mass of diisocyanate and hydroxy acrylate as inhibitor (p-hydroxyanisole), raise the temperature to 40-60°C and react for 1-3 hours to obtain a semi-adduct of diisocyanate and hydroxyethyl acrylate, and calculate the theoretical NCO equivalent.
[0027] S2: Add epoxy resin and mercaptosilane coupling agent into reactor B in a molar ratio of epoxy bond to mercapto group of 1:1, add catalyst (triethylamine) in an amount of 0.01-0.2% of the total mass of epoxy resin and mercaptosilane coupling agent, raise the temperature to 70-90°C and react for 1-3 hours to obtain siloxane-modified epoxy resin, and calculate the theoretical hydroxyl equivalent.
[0028] S3: According to the calculation method of NCO equivalent: hydroxyl equivalent = semi-adduct mass: siloxane-modified epoxy resin mass, a set amount of siloxane-modified epoxy resin is added to reactor A, 0.01-0.2% of the total mass of the siloxane-modified epoxy resin is added as catalyst (dibutyltin dilaurate) and 0.01-0.2% of the total mass of the siloxane-modified epoxy resin is added as inhibitor (p-hydroxyanisole), the reaction is maintained at 60-80°C with stirring for 2-8h, and an infrared spectrometer is used to detect the concentration of 2260cm -1 After the isocyanate absorption peaks of about 50 Å disappear, the siloxane-epoxy resin modified polyurethane acrylate is obtained.
[0029] Wherein, in step S1, the diisocyanate includes one or more of hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI), toluene diisocyanate (T100 / T80 / T65), xylene diisocyanate (XDI), trimethylol diisocyanate (TMDI), 1,5-naphthalene diisocyanate (NDI), and diphenylmethane diisocyanate (MDI-100 / MDI-50).
[0030] Wherein, in step S1, the hydroxy acrylate includes one or more of 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 3-hydroxypropyl acrylate, 2-hydroxybutyl acrylate, and 4-hydroxybutyl acrylate.
[0031] Among them, in step S1, the epoxy resin refers to a substance containing an epoxy bond in its molecular structure, including one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol E epoxy resin, bisphenol S epoxy resin, epoxy soybean oil, cardanol modified epoxy resin, trimethylolpropane triglycidyl ether, hexanediol diglycidyl ether, and phenyl glycidyl ether.
[0032] Wherein, in step S2, the mercaptosilane coupling agent includes one or more of mercaptopropyltrimethoxysilane, mercaptopropyltriethoxysilane, mercaptopropylmethyldimethoxysilane, and mercaptopropylmethyldiethoxysilane.
[0033] Wherein, in step S1, 0-30% of the total mass of diisocyanate and hydroxy acrylate is added to the acrylate monomer; in step S2, 0-30% of the total mass of epoxy resin and mercaptosilane coupling agent is added to the acrylate monomer;
[0034] or
[0035] In step S1, 0-30% of the total mass of diisocyanate and hydroxy acrylate is added to the acrylate monomer; in step S3, 0-30% of the total mass of siloxane-modified epoxy resin is added to the acrylate monomer;
[0036] or
[0037] In step S2, 0-30% of the total mass of the epoxy resin and the mercaptosilane coupling agent is added to the acrylate monomer; in step S3, 0-30% of the total mass of the siloxane-modified epoxy resin is added to the acrylate monomer;
[0038] or
[0039] In step S1, 0-30% of the total mass of diisocyanate and hydroxy acrylate is added to the acrylate monomer; in step S2, 0-30% of the total mass of epoxy resin and mercaptosilane coupling agent is added to the acrylate monomer; in step S3, 0-30% of the total mass of siloxane-modified epoxy resin is added to the acrylate monomer.
[0040] Wherein, in step S1, 0-30% of the total mass of diisocyanate and hydroxy acrylate is added to the acrylate monomer; or
[0041] In step S2, 0-30% of the total weight of the epoxy resin and the mercaptosilane coupling agent is added to the acrylate monomer; or
[0042] In step S3, 0-30% of the total mass of the siloxane-modified epoxy resin is added with an acrylate monomer;
[0043] The acrylate monomer is an acrylate monomer with 1-6 functions and does not contain a hydroxyl structure, including one or more of isobornyl acrylate, 2-cyclohexyl acrylate, 3,3,5-trimethylcyclohexyl acrylate, trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, tripropylene glycol diacrylate, dipropylene glycol diacrylate, 1,6-hexanediol diacrylate, isobornyl methacrylate, and tetrahydrofurfuryl methacrylate.
[0044] In the above technical solution, the thermal runaway protection material is cut into suitable sizes according to the structure of the battery pack and packaged in a sealed and pressure-resistant shell; according to the application scenario of the energy storage battery, it is packaged with independent thermal runaway protection materials, or packaged after being bonded with thermal insulation buffer materials to increase the compression ratio of the thermal protection material and buffer the expansion and extrusion of the battery.
[0045] In the above technical solution, the thermal runaway protection material is used alone as a thermal runaway protection material, or is combined with a thermal insulation material or a physical thermal insulation structure to form a thermal protection system, and the thermal runaway protection material serves as a heat-absorbing material in the thermal protection system.
[0046] The thermal runaway protection material of the present invention is used for thermal runaway protection of various batteries, preferably lithium-ion batteries and sodium-ion batteries.
[0047] Compared with the prior art, the present invention has the following beneficial effects:
[0048] 1. The thermal runaway protection material of the present invention uses photocuring rapid prototyping to shape the pressed high-density material, and can be designed according to different battery structures to meet the needs of different scenarios.
[0049] 2. When a battery experiences thermal runaway, the thermal runaway protection material of the present invention can prevent the spread of thermal runaway and reduce the impact on adjacent batteries.
[0050] 3. Since most of the heat-absorbing materials are powder or block crystals, and long-term exposure to the air will cause the volatilization of crystal water and the volume and shape changes caused by absorbing water under high humidity, which does not match the shape and size required by the battery pack and cannot be used directly. The thermal runaway protection material described in the present invention is an organic-inorganic composite material. UV curing encapsulation resin is coated on the surface of the heat-absorbing material to achieve stable encapsulation of the heat-absorbing material. After ultraviolet light irradiation, the spherical silicon powder inside the bonding resin can guide ultraviolet light into the deep layer to achieve dual curing, which meets the one-time curing and molding of the 40mm thick thermal runaway protection material.
[0051] 4. The thermal runaway protection material of the present invention has a high endothermic enthalpy (the endothermic enthalpy of the endothermic material is > 1200 J / g). A chemical reaction will occur between 90-400°C and the material will actively absorb heat. When the temperature reaches above 90°C, the material will spontaneously endothermically decompose, forming a continuous endothermic effect, driving the temperature of the runaway battery pack to drop. After the decomposition of the protection material is complete, a porous structure will be formed on the surface of the material, making it an excellent thermal insulation material, preventing heat from being transferred to adjacent batteries, preventing adjacent batteries from continuing to heat up, and avoiding fire and explosion. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] The present invention will be further described below in conjunction with the accompanying drawings and embodiments:
[0053] Figure 1 It is a schematic diagram of the curing process of the thermal runaway protection material of the present invention;
[0054] In the figure, heat absorbing material 1, spherical silicon powder 2, polyvinyl alcohol 3, light transmitting spherical silicon powder 4, UV curing encapsulation resin (before curing) 5, UV curing encapsulation resin (after curing) 6;
[0055] Figure 2 It is a schematic diagram of the endothermic decomposition process of the thermal runaway protection material of the present invention;
[0056] In the figure, endothermic material 1, endothermic material decomposition residue 2, polyvinyl alcohol 3, UV curing encapsulation resin (after curing) 4, spherical silicon powder 5, pores formed after decomposition of endothermic material 6;
[0057] Figure 3 It is a schematic diagram of the test device of the present invention. DETAILED DESCRIPTION
[0058] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0059] Some of the special raw materials used in the following examples are shown in Table 1.
[0060] Table 1
[0061]
[0062]
[0063] The siloxane-epoxy resin composite modified polyurethane acrylate and silane modified resin used in the present invention are specifically prepared by the following method:
[0064] 1. Preparation of Siloxane-Epoxy Resin Composite Modified Polyurethane Acrylate
[0065] S1: 444.58 g (2 mol) of isophorone diisocyanate, 236.98 g (2 mol, purity 98%) of 2-hydroxyethyl acrylate, 0.4 g of catalyst (dibutyltin dilaurate) and 0.5 g of inhibitor (p-hydroxyanisole) were added to reactor A, and the temperature was raised to 40-45° C. for reaction for 3 hours to obtain a semi-adduct of diisocyanate and hydroxyethyl acrylate, and the calculated theoretical NCO equivalent was 341.23 g / mol;
[0066] S2: Add 510 g (1.5 mol of bisphenol F epoxy resin, 3 mol of epoxy bond) of bisphenol F epoxy resin, 841.11 g (3 mol) of mercaptopropyl triethoxysilane and 1.35 g of catalyst (triethylamine) into reactor B, heat to 85° C. and react for 2.5 hours to obtain siloxane-modified epoxy resin for standby use. The calculated theoretical hydroxyl equivalent is 450.82 g / mol.
[0067] S3: According to the calculation method of NCO equivalent: hydroxyl equivalent = semi-adduct mass: siloxane-modified epoxy resin mass, 682.46g of semi-adduct was obtained in reactor A. 901.64g of siloxane-modified epoxy resin was added to reactor A, 180g of 1,6-hexanediol diacrylate, 0.7g of catalyst (dibutyltin dilaurate), and 0.9g of inhibitor (p-hydroxyanisole) were added, and the reaction was stirred at 70-75℃ for 4h. The infrared spectrometer was used to detect the concentration of 2260cm -1 After the isocyanate absorption peaks of about 1:1 and 2:1 disappear, the siloxane-epoxy resin composite modified polyurethane acrylate Si / EP-PUA-1 is obtained.
[0068] 2. Preparation of silane-modified resin G-PUA-1
[0069] 560.74 g of mercaptopropyl triethoxysilane and 222.29 g of isophorone diisocyanate were added into a reactor, and 0.7 g of dibutyltin dilaurate was added. The reaction was maintained at 85° C. for 4.5 hours to obtain the silane-modified resin G-PUA-1.
[0070] 3. Preparation of silane-modified resin G-PUA-2
[0071] 392.68 g of mercaptopropyltrimethoxysilane and 222.29 g of isophorone diisocyanate were added into a reactor, and 0.53 g of dibutyltin dilaurate was added, and the reaction was maintained at 85° C. for 4.5 hours to obtain the silane-modified resin G-PUA-2.
[0072] Embodiment 1:
[0073] A rapid prototyping thermal runaway protection material and composition, comprising, by mass percentage: 30% citric acid, 52% magnesium chloride hexahydrate, 7.9% polyvinyl alcohol, 0.1% eicosanedioic acid, and 10% UV curing encapsulation resin UV-1. The preparation method thereof is as follows:
[0074] S1: Add 300 g citric acid, 520 g magnesium chloride hexahydrate, 79 g polyvinyl alcohol, 1 g eicosanedioic acid, and 100 g UV curable encapsulation resin UV-1 into a mixing kettle and mix well;
[0075] S2: Pour the mixture into a mold of 227 mm × 160 mm × 2 mm and use the mold to press into shape under a hydraulic press. The feed mass is 110 g and the pressure is 10.6 MPa.
[0076] S3: After demoulding the pressed material, place it at 100mW / cm 2 The irradiation was carried out under a metal halide lamp for 40 seconds, and the irradiation dose was 4J / cm 2 After CNC (numerical control machine tool) grinding, the thermal protection material RF-A2 with a flat and smooth surface is obtained.
[0077] The UV curing encapsulation resin UV-1 comprises, by mass percentage: 41.2% of siloxane-epoxy resin composite modified polyurethane acrylate Si / EP-PUA-1, 1% of bisphenol A epoxy resin, 33% of epoxy acrylate, 1% of acrylic acid, 9% of active monomer (trimethylolpropane triacrylate), 5% of active monomer (dipropylene glycol diacrylate), 0.2% of hexadecanedioic acid, 2% of silane modified resin GPUA-1, 0.5% of p-toluenesulfonyl isocyanate, 5% of spherical silicon powder, 1% of photoinitiator (184), 1% of 4-acryloxybenzophenone, 1% of photoinitiator (TPO), and 0.1% of polymerization inhibitor (p-hydroxyanisole). The preparation method thereof is as follows:
[0078] 412 g of siloxane-epoxy resin composite modified polyurethane acrylate Si / EP-PUA-1, 10 g of bisphenol A epoxy resin, 330 g of epoxy acrylate (CN120 NS), 10 g of acrylic acid, 90 g of active monomer (trimethylolpropane triacrylate), 50 g of active monomer (tripropylene glycol diacrylate), 2 g of hexadecanedioic acid, 20 g of silane modified resin (GPUA-1), 5 g of p-toluenesulfonyl isocyanate, 50 g of spherical silica powder, 10 g of photoinitiator (184), 10 g of 4-acryloxybenzophenone, 10 g of photoinitiator (TPO), and 1 g of inhibitor (p-hydroxyanisole) were added into a reactor, the mixture was stirred at 55° C. for 2.5 hours, 5 g of p-toluenesulfonyl isocyanate was added, and the mixture was stirred for 20 minutes to obtain a UV curable encapsulation resin UV-1.
[0079] The thermal conductivity, enthalpy value, density, average thickness and compressive strength of the thermal runaway protection material RF-A2 prepared in this embodiment are measured and are shown in Table 2.
[0080] Embodiment 2:
[0081] A rapid prototyping thermal runaway protection material and composition, comprising, by mass percentage: 85% potassium aluminum sulfate dodecahydrate, 6.5% polyvinyl alcohol, 0.5% hexadecanedioic acid, and 8% UV curing encapsulation resin UV-1. The preparation method thereof is as follows:
[0082] S1: Add 850g of potassium aluminum sulfate dodecahydrate, 65g of polyvinyl alcohol, 5g of hexadecanedioic acid, and 80g of UV curable encapsulation resin UV-1 into a mixing kettle and mix well;
[0083] S2: Pour the mixture into a 227mm×160mm×5mm mold with a polytetrafluoro coating on the surface, and use the mold to press and mold under a hydraulic press. The feed mass is 292.5g and the pressure is 8.7MPa;
[0084] S3: After demoulding the pressed material, place it at 100mW / cm 2The irradiation was carried out under a metal halide lamp for 40 seconds, and the irradiation dose was 4J / cm 2 After CNC (numerical control machine tool) grinding, the thermal runaway protection material RF-B5 with a smooth surface is obtained.
[0085] The UV curing encapsulation resin UV-1 and its preparation method are the same as those in Example 1.
[0086] The thermal conductivity, enthalpy value, density, average thickness and compressive strength of the thermal runaway protection material RF-B5 prepared in this embodiment are shown in Table 2.
[0087] Embodiment 3:
[0088] A rapid prototyping thermal runaway protection material and composition, comprising by mass percentage: 30% citric acid, 54% magnesium chloride hexahydrate, 8% polyvinyl alcohol, and 8% UV curing encapsulation resin UV-3. The preparation method thereof is as follows:
[0089] S1: Add 600g of citric acid, 1080g of magnesium chloride hexahydrate, 160g of polyvinyl alcohol, and 160g of UV curable encapsulation resin UV-2 into a mixing kettle and mix well;
[0090] S2: Pour the mixture into a 227 mm × 160 mm × 15 mm mold and use the mold to press the mold under a hydraulic press. The feed mass is 817.5 g and the pressure is 12.0 MPa;
[0091] S3: After demoulding the pressed material, place it at 100mW / cm 2 The irradiation was carried out under a metal halide lamp for 60 seconds, and the irradiation dose was 6J / cm 2 After CNC (numerical control machine tool) grinding, the thermal runaway protection material RF-C15 with a smooth surface is obtained.
[0092] The UV curing encapsulation resin UV-3 comprises, by mass percentage, 31.0% of siloxane-epoxy resin composite modified polyurethane acrylate Si / EP-PUA-1, 4% of hexanediol diglycidyl ether, 10% of epoxy acrylate (CN120 NS), 25% of active monomer (trimethylolpropane triacrylate), 0.4% of octadecane dioic acid, 20% of silane modified resin (GPUA-1), 2.0% of p-toluenesulfonyl isocyanate, 5% of spherical silicon powder, 1% of 4-acryloxybenzophenone, 1.4% of photoinitiator (TPO), and 0.2% of polymerization inhibitor (p-hydroxyanisole). The preparation method is the same as that of UV-1 in Example 1.
[0093] The thermal conductivity, enthalpy value, density, average thickness and compressive strength of the thermal runaway protection material RF-C15 prepared in this embodiment are shown in Table 2.
[0094] Embodiment 4:
[0095] A rapid prototyping thermal runaway protection material and composition, comprising, by mass percentage: 85.7% potassium aluminum sulfate dodecahydrate, 7% polyvinyl alcohol, 0.3% eicosanedioic acid, and 7% UV-curable encapsulation resin UV-2. The preparation method thereof is as follows:
[0096] S1: Add 1714 g of potassium aluminum sulfate dodecahydrate, 140 g of polyvinyl alcohol, 6 g of eicosanedioic acid, and 140 g of UV curable encapsulation resin UV-2 into a mixing kettle and mix well;
[0097] S2: Pour the mixture into a 227mm×160mm×30mm mold and use the mold to press and mold under a hydraulic press. The feed mass is 1744g and the pressure is 9.5MPa;
[0098] S3: After demoulding the pressed material, place it at 100mW / cm 2 The irradiation was carried out under a metal halide lamp for 80 seconds, and the irradiation dose was 8J / cm 2 After CNC (numerical control machine tool) grinding, the thermal runaway protection material RF-D30 with a smooth surface is obtained.
[0099] The UV curing encapsulation resin UV-2 comprises, by mass percentage: 46.6% of siloxane-epoxy resin composite modified polyurethane acrylate Si / EP-PUA-1, 10% of epoxy acrylate (CN120 NS), 10% of active monomer (trimethylolpropane triacrylate), 12% of active monomer (tripropylene glycol diacrylate), 0.3% of eicosanedioic acid, 10% of silane modified resin (GPUA-2), 1% of p-toluenesulfonyl isocyanate, 8% of spherical silicon powder, 0.5% of photoinitiator 184, 1.5% of photoinitiator TPO, and 0.1% of polymerization inhibitor (p-hydroxyanisole). The preparation method is the same as that of UV-1 in Example 1.
[0100] The thermal conductivity, enthalpy value, density, average thickness and compressive strength of the thermal runaway protection material RF-D30 prepared in this embodiment are shown in Table 2.
[0101] Comparative Example 1:
[0102] A rapid-prototyping thermal runaway protection material and composition, comprising, by mass percentage, 30% citric acid, 52% magnesium chloride hexahydrate, 7.9% polyvinyl alcohol, 0.1% eicosanedioic acid, and 10% UV-curable encapsulation resin UV-5. The preparation method, feeding mass and pressure, and radiation dose thereof are the same as those in Example 1.
[0103] The UV curing encapsulation resin UV-5 comprises, by mass percentage, 20.0% of siloxane-epoxy resin composite modified polyurethane acrylate Si / EP-PUA-1, 10% of bisphenol F epoxy resin, 13% of epoxy acrylate (CN120 NS), 7% of acrylic acid, 9% of active monomer (trimethylolpropane triacrylate), 2.2% of hexadecanedioic acid, 29% of silane modified resin GPUA-2, 1% of p-toluenesulfonyl isocyanate, 4.7% of spherical silicon powder, 1% of photoinitiator 184, 2% of 4-acryloxybenzophenone, 1% of photoinitiator (TPO), and 0.1% of polymerization inhibitor (p-hydroxyanisole). The preparation method is the same as that of UV-1 in Example 1.
[0104] The thermal conductivity, enthalpy value, density, average thickness and compressive strength of the thermal runaway protection material RF-E2 prepared in this embodiment are shown in Table 2.
[0105] Comparative Example 2:
[0106] A rapid prototyping thermal runaway protection material and composition, comprising, by mass percentage: 85% of potassium aluminum sulfate dodecahydrate, 6.5% of polyvinyl alcohol, 0.5% of hexadecanedioic acid, and 8% of UV curing encapsulation resin UV-6. The preparation method, feeding mass and pressure, and radiation dose thereof are the same as those in Example 2.
[0107] The UV curing encapsulation resin UV-6 comprises, by mass percentage, 80.1% of siloxane-epoxy resin composite modified polyurethane acrylate Si / EP-PUA-1, 4% of epoxy acrylate (CN120 NS), 6% of active monomer (trimethylolpropane triacrylate), 2% of active monomer (tripropylene glycol diacrylate), 0.3% of eicosanedioic acid, 2% of silane modified resin (GPUA-2), 1% of p-toluenesulfonyl isocyanate, 3% of spherical silicon powder, 0.5% of photoinitiator (184), 1% of 4-acryloxybenzophenone, and 0.1% of polymerization inhibitor (p-hydroxyanisole). The preparation method is the same as that of UV-1 in Example 1.
[0108] The thermal conductivity, enthalpy value, density, average thickness and compressive strength of the thermal runaway protection material RF-F5 prepared in this embodiment are shown in Table 2.
[0109] Comparative Example 3:
[0110] A rapid-prototyping thermal runaway protection material and composition, comprising, by mass percentage, 30% citric acid, 54% magnesium chloride hexahydrate, 8% polyvinyl alcohol, and 8% UV-curable encapsulation resin UV-4. The preparation method, feeding mass and pressure, and radiation dose thereof are the same as those in Example 3.
[0111] The UV curing encapsulation resin UV-4 comprises, by mass percentage, 1.2% of polyurethane acrylate Changxing 6148-J754, 1.0% of bisphenol A epoxy resin, 33% of epoxy acrylate, 9% of active monomer (trimethylolpropane triacrylate), 5% of active monomer (dipropylene glycol diacrylate), 0.2% of hexadecanedioic acid, 2.5% of silane modified resin (GPUA-2), 0.5% of p-toluenesulfonyl isocyanate, 5% of spherical silicon powder, 1% of photoinitiator (184), 0.5% of 4-acryloxybenzophenone, 1% of photoinitiator (TPO), and 0.1% of polymerization inhibitor (p-hydroxyanisole). The preparation method is the same as that of UV-1 in Example 1.
[0112] The thermal conductivity, enthalpy value, density, average thickness and compressive strength of the thermal runaway protection material RF-G15 prepared in this embodiment are shown in Table 2.
[0113] Table 2 shows the performance test results of the thermal runaway protection materials prepared in Examples 1-4 and Comparative Examples 1-3.
[0114] Table 2 Performance tests of embodiments and comparative examples
[0115]
[0116]
[0117] Note: ① Thermal conductivity refers to ISO 22007-2 test
[0118] ② The enthalpy value of the heat-absorbing material is tested by differential scanning calorimetry
[0119] ③ Density = weight / volume
[0120] ④Compression strength test according to GB / T 1041-2008
[0121] Test example
[0122] In order to test the thermal runaway effect of the thermal runaway protection material of the present invention, the following test platform was built: two soft-pack lithium iron phosphate batteries with dimensions of 227*160*7.25mm, a standard voltage of 3.3V, and a fully charged capacity of 20AH, which were numbered 1 and 2 respectively. The thermal runaway protection material prepared in the embodiment is sandwiched between battery No. 1 and battery No. 2, a heating plate with a power of 500W is attached to the right side of battery No. 1, and fixed with upper and lower fixing fixtures, and the two batteries are connected to a signal acquisition device to collect the voltage of the two batteries and the temperature of the fitting surface of the two batteries and the thermal runaway protection material. A blank sample without the thermal runaway protection material and a sample of 2mm glass fiber aerogel are also made. Its structure is as follows Figure 3 shown.
[0123] The test steps are as follows: put the heating plate and the battery pack into an oven at 50±2℃, keep the temperature constant for 12 hours, power on the heating plate for heating, set the heating plate temperature power to 100%, and collect the battery voltage and temperature. When the voltage of battery No. 1 becomes 0V, stop heating, continue to collect the battery temperature, and stop collecting data until the temperature of both batteries drops below 50℃. The results are shown in Table 3.
[0124] Table 3 Application test of embodiments and comparative examples
[0125]
[0126]
[0127] The test shows that the blank sample did not use thermal runaway protection materials. When the heating plate was heated for 222s, battery No. 1 was in complete thermal runaway, and the maximum temperature of the battery reached 385°C, and the adjacent battery No. 2 also experienced thermal runaway. The sample using glass fiber aerogel had a faster internal temperature rise due to the thermal insulation effect of the aerogel, and it was in complete thermal runaway in 196s. The maximum temperature also reached 475°C, which was 90°C higher than the blank sample, and the adjacent battery No. 2 also experienced thermal runaway.
[0128] In the test samples using the 2mm, 5mm, 15mm and 30mm thermal runaway protection materials of the present invention, the adjacent No. 2 batteries did not have thermal runaway, and the time for the No. 1 battery voltage to drop to 0 was nearly twice as long as that of the blank sample. During the entire test process, the maximum battery temperature was 284°C and the minimum was 232°C, which was more than 100°C lower than the blank sample temperature. After the test, the thermal conductivity of the thermal runaway protection material increased with increasing thickness, indicating that after the thickness increased, there was a surplus of material, and the protection material close to the No. 2 battery had a better thermal insulation effect. The maximum temperature of the adjacent No. 2 battery was 118°C and the minimum was 72°C, which was lower than the thermal runaway temperature of 150°C for lithium iron phosphate batteries reported in the literature (Mei Wenxin et al., Simulation study on high-temperature thermal runaway of large lithium iron phosphate batteries [J]. Energy Storage Science and Technology, 2021, 10(1): 202-209).
[0129] However, due to the low compression strength of the protective materials used in the comparison group of 2mm, 5mm, and 15mm, the materials were squeezed and cracked during the test, and then squeezed out, resulting in incomplete fit between the material and the battery and a decrease in the amount of material. Although the time for the voltage of battery No. 1 to drop to 0 was eventually extended, it eventually caused thermal runaway of battery No. 2.
[0130] The above test results fully demonstrate that the thermal runaway protection material of the present invention first absorbs heat to quickly reduce the battery temperature, and then insulates to prevent heat from being transferred to adjacent batteries, which has a significant effect on preventing the spread of battery thermal runaway.
[0131] The above embodiments are only preferred technical solutions of the present invention and should not be regarded as limiting the present invention. The protection scope of the present invention shall be the technical solutions recorded in the claims, including equivalent replacement solutions of the technical features in the technical solutions recorded in the claims. That is, equivalent replacement improvements within this scope are also within the protection scope of the present invention.
Claims
1. A rapid prototyping thermal runaway protection material and composition, characterized in that: The composition comprises, by mass percentage, 71-95% of heat absorbing material, 1.5-12% of polyvinyl alcohol, 0-1% of long-chain alkyl diacid and 3-16% of UV curing encapsulation resin; the preparation method thereof is as follows: Add all the materials in the formula into a mixing kettle, mix them evenly, press them into shape in a mold, and cure them under ultraviolet light to obtain a thermal runaway protection material.
2. The thermal runaway protection material and composition according to claim 1, characterized in that: The ultraviolet lamp is a high-pressure mercury lamp or a metal halide lamp.
3. The thermal runaway protection material and composition according to claim 2, characterized in that: The ultraviolet lamp is an ultraviolet lamp in the 365-405nm band.
4. The thermal runaway protection material and composition according to claim 1, characterized in that: The heat absorbing material includes one or more of sodium acetate trihydrate, ammonium ferric oxalate trihydrate, citric acid monohydrate, citric acid, oxalic acid dihydrate, anhydrous oxalic acid, malonic acid, magnesium sulfate heptahydrate, zinc sulfate heptahydrate, succinic acid, maleic acid, fumaric acid, sodium carbonate decahydrate, calcium chloride hexahydrate, aluminum nitrate nonahydrate, ammonium pentaborate octahydrate, ammonium ferric sulfate dodecahydrate, ferrous chloride tetrahydrate, ammonium oxalate monohydrate, sodium tetraborate decahydrate, sodium tetraborate pentahydrate, aluminum sulfate octahydrate, ammonium pentaborate, ammonium hydrogen borate tetrahydrate, boric acid, barium hydroxide octahydrate, sodium silicate pentahydrate, silicic acid, hydrated silicic acid, ammonium aluminum sulfate dodecahydrate, hydrated sodium aluminum silicate, potassium aluminum sulfate dodecahydrate, sodium sulfate decahydrate, copper sulfate heptahydrate, ferrous sulfate heptahydrate, cobalt chloride hexahydrate, calcium sulfate dihydrate, etc.; The polyvinyl alcohol is in powder form.
5. The thermal runaway protection material and composition according to claim 1, characterized in that: The UV curing encapsulation resin comprises, by mass percentage, 25-70% of siloxane-epoxy resin composite modified polyurethane acrylate, 0-5% of epoxy resin, 5-40% of epoxy acrylate, 0-5% of acrylic acid, 5-30% of active monomer, 0-1% of long-chain alkyl diacid, 0-25% of silane modified resin, 0.1-3% of dewatering agent, 0-10% of spherical silicon micropowder, 0.1-3% of photoinitiator and 0.01-0.3% of polymerization inhibitor; and the preparation method thereof is as follows: adding the above components into a reactor according to a proportion, maintaining stirring at 50-60° C. for 2-3 hours, adding the dewatering agent, stirring for 10-30 minutes, and obtaining the UV curing encapsulation resin.
6. The thermal runaway protection material and composition according to claim 5, characterized in that: The epoxy resin includes one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol E epoxy resin, bisphenol S epoxy resin, epoxy soybean oil, cardanol modified epoxy resin, trimethylolpropane triglycidyl ether, hexanediol diglycidyl ether, and phenyl glycidyl ether; The epoxy acrylate includes CN104 NS or CN120 NS of Sartomer; The active monomers include one or more of isobornyl acrylate, 2-cyclohexyl acrylate, 3,3,5-trimethylcyclohexyl acrylate, trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, tripropylene glycol diacrylate, dipropylene glycol diacrylate, 1,6-hexanediol diacrylate, isobornyl methacrylate, and tetrahydrofurfuryl methacrylate; The long-chain alkyl diacid includes one or more of dodecanedioic acid, tetradecanedioic acid, hexadecanedioic acid, octadecanedioic acid, and eicosanedioic acid.
7. The thermal runaway protection material and composition according to claim 5, characterized in that: The silane-modified resin includes one or more of silane-modified polyether resin, silane-modified polyacrylate resin, silane-modified polyurethane resin, silane-modified polyester resin, and alkoxy silicone resin.
8. The thermal runaway protection material and composition according to claim 5, characterized in that: The dewatering agent is p-toluenesulfonyl isocyanate; The spherical silicon powder is a spherical silicon powder with D50=50-300μm and D100<500μm; The photoinitiator includes one or more of 4-benzoyl-4'-methyl-diphenyl sulfide, 2,4,6-trimethylbenzoyldiphenyl phosphine oxide, 2,4,6-trimethylbenzoylphosphonic acid ethyl ester, bis(2,4,6-trimethylbenzyl acyl)phenyl phosphine oxide, benzoin dimethyl ether, 2-methyl-1-(4-methylmercaptophenyl)-2-morpholine-1-propanone, polymerized [2-hydroxy-2-methyl-1-[4-(1-methylvinyl)phenyl]acetone], 2,4,6-trimethylbenzoyl-di(p-tolyl)phosphine oxide, 1-(9,9-dibutyl-9H-fluorene-2-yl)-2-methyl-2-morpholine-4-yl-propane-1-one, 1-hydroxycyclohexyl benzophenone, 4-acryloxybenzophenone, and methyl o-benzoylbenzoate; The polymerization inhibitor is p-hydroxyanisole.
9. The thermal runaway protection material and composition according to claim 5, characterized in that: The preparation method of the siloxane-epoxy resin composite modified polyurethane acrylate is as follows: S1: adding diisocyanate and hydroxy acrylate into reactor A in a molar ratio of 1:1, adding 0.01-0.2% of the total mass of diisocyanate and hydroxy acrylate as catalyst (dibutyltin dilaurate) and 0.01-0.2% of the total mass of diisocyanate and hydroxy acrylate as inhibitor (p-hydroxyanisole), heating to 40-60° C. for reaction for 1-3 hours to obtain a semi-adduct of diisocyanate and hydroxyethyl acrylate, and calculating the theoretical NCO equivalent; S2: adding epoxy resin and mercaptosilane coupling agent into reactor B in a molar ratio of epoxy bond to mercapto group of 1:1, adding catalyst (triethylamine) of 0.01-0.2% of the total mass of epoxy resin and mercaptosilane coupling agent, heating to 70-90° C. for reaction for 1-3 hours to obtain siloxane-modified epoxy resin, and calculating theoretical hydroxyl equivalent; S3: According to the calculation method of NCO equivalent: hydroxyl equivalent = semi-adduct mass: siloxane-modified epoxy resin mass, a set amount of siloxane-modified epoxy resin is added into reactor A, 0.01-0.2% of the total mass of the siloxane-modified epoxy resin is added as a catalyst (dibutyltin dilaurate) and 0.01-0.2% of the total mass of the siloxane-modified epoxy resin is added as an inhibitor (p-hydroxyanisole), and the reaction is stirred at 60-80° C. for 2-8 hours until the isocyanate reaction is completed to obtain the siloxane-epoxy resin modified polyurethane acrylate.
10. The thermal runaway protection material and composition according to claim 9, characterized in that: In step S1, the diisocyanate includes one or more of hexamethylene diisocyanate, isophorone diisocyanate, toluene diisocyanate, xylylene diisocyanate, trimethylhexane diisocyanate, 1,5-naphthalene diisocyanate, and diphenylmethane diisocyanate; The hydroxy acrylate includes one or more of 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 3-hydroxypropyl acrylate, 2-hydroxybutyl acrylate, and 4-hydroxybutyl acrylate.
11. The thermal runaway protection material and composition according to claim 9, characterized in that: In step S2, the mercaptosilane coupling agent includes one or more of mercaptopropyltrimethoxysilane, mercaptopropyltriethoxysilane, mercaptopropylmethyldimethoxysilane, and mercaptopropylmethyldiethoxysilane.
12. The thermal runaway protection material and composition according to claim 9, characterized in that: In step S1, 0-30% of the total mass of diisocyanate and hydroxy acrylate is added to the acrylate monomer; in step S2, 0-30% of the total mass of epoxy resin and mercaptosilane coupling agent is added to the acrylate monomer; or In step S1, 0-30% of the total mass of diisocyanate and hydroxy acrylate is added to the acrylate monomer; in step S3, 0-30% of the total mass of siloxane-modified epoxy resin is added to the acrylate monomer; or In step S2, 0-30% of the total mass of the epoxy resin and the mercaptosilane coupling agent is added to the acrylate monomer; in step S3, 0-30% of the total mass of the siloxane-modified epoxy resin is added to the acrylate monomer; or In step S1, 0-30% of the total mass of diisocyanate and hydroxy acrylate is added to the acrylate monomer; in step S2, 0-30% of the total mass of epoxy resin and mercaptosilane coupling agent is added to the acrylate monomer; in step S3, 0-30% of the total mass of siloxane-modified epoxy resin is added to the acrylate monomer. The acrylate monomer is an acrylate monomer with 1-6 functions and does not contain a hydroxyl structure, including one or more of isobornyl acrylate, 2-cyclohexyl acrylate, 3,3,5-trimethylcyclohexyl acrylate, trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, tripropylene glycol diacrylate, dipropylene glycol diacrylate, 1,6-hexanediol diacrylate, isobornyl methacrylate, and tetrahydrofurfuryl methacrylate.
13. The thermal runaway protection material and composition according to claim 9, characterized in that: In step S1, 0-30% of the total weight of diisocyanate and hydroxy acrylate is added to the acrylate monomer; or In step S2, 0-30% of the total weight of the epoxy resin and the mercaptosilane coupling agent is added to the acrylate monomer; or In step S3, 0-30% of the total mass of the siloxane-modified epoxy resin is added with an acrylate monomer; The acrylate monomer is an acrylate monomer with 1-6 functions and does not contain a hydroxyl structure, including one or more of isobornyl acrylate, 2-cyclohexyl acrylate, 3,3,5-trimethylcyclohexyl acrylate, trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, tripropylene glycol diacrylate, dipropylene glycol diacrylate, 1,6-hexanediol diacrylate, isobornyl methacrylate, and tetrahydrofurfuryl methacrylate.
14. The thermal runaway protection material and composition according to any one of claims 1 to 13, characterized in that: The thermal runaway protection material is cut into suitable sizes according to the structure of the battery pack and packaged in a sealed and pressure-resistant shell.
15. The thermal runaway protection material and composition according to any one of claims 1 to 13, characterized in that: The thermal runaway protection material is used alone as a thermal runaway protection material, or is used in combination with a thermal insulation material or a physical thermal insulation structure to form a thermal protection system.
Citation Information
Cited By
Environment-friendly water system fire-fighting thermal runaway protection composite material and preparation method thereof
CN122080581A
